Letter to Jane Tolmach from Roy F. Greenaway - Roy F. Greenaway:::::: (1971)
In this January 5, 1971 letter, Roy F. Greenaway, Administrative Assistant to Senator Alan Cranston, acknowledges Jane Tolmach's invitation for Cranston to be the special guest at the DSCC Key Women award luncheon on January 16. Although Cranston is pleased by the invitation, he is unable to attend due to a prior commitment in Los Angeles. Greenaway closes by expressing appreciation for hearing from her and noting he will see her in Sacramento.